ANALISA HEAD LOSS DAN KERJA POMPA DENGAN VARIASI PERUBAHAN DIAMETER PADA SISTEM PEMIPAAN - Agung Kurnia Yahya; Puji Rahayu; Hasnah Ulia; Achmad Yanuar Maulana (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2022)
Fluids often experience a loss of energy (head loss) in the pipe due to flow turbulence, which results in friction on the inner surface of the pipe. Head loss is very detrimental in piping systems because it can reduce the level of fluid flow efficiency. Head loss is affected by variations in bends (elbows), joints, valves, and pipe diameters. The purpose of this study is to determine the head loss that occurs in each line of the fluid flow piping system, which consists of variations in the cross-sectional area of the pipe and the number of connections, valves, and bends. In addition, it is also used to evaluate pump work in series and complex circuits. The smaller the diameter, the more the fluid velocity increases, causing the friction in the pipe to increase and the head loss to increase. The pump work required to flow the fluid is directly proportional to the amount of head loss that occurs in the piping system.